2022
DOI: 10.1038/s41467-022-30264-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the CDK2 and Cyclin A complex leads to autophagic degradation of CDK2 in cancer cells

Abstract: Cyclin-dependent kinase 2 (CDK2) complex is significantly over-activated in many cancers. While it makes CDK2 an attractive target for cancer therapy, most inhibitors against CDK2 are ATP competitors that are either nonspecific or highly toxic, and typically fail clinical trials. One alternative approach is to develop non-ATP competitive inhibitors; they disrupt interactions between CDK2 and either its partners or substrates, resulting in specific inhibition of CDK2 activities. In this report, we identify two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…Recent work has shown that the complex natural product homoharringtonine (HHT) disrupts the PPI between CDK2 and cyclin A to act as an efficacious anticancer agent, although the allosteric binding mode of HHT has not been experimentally confirmed outside of computational models and its selectivity amongst kinases not explored. 36 Additionally, disrupting the CDK2/cyclin interaction may be less toxic than traditional ATP-site inhibitors that sequester cyclin via their positive cooperativity with cyclin binding. 16 Further development of our allosteric inhibitors might confer an advantage in this regard compared to other promising compounds, such as recently developed CDK2/cyclin E1 inhibitor PF-07104091, a selective ATP-site inhibitor targeting the cyclin-bound activated state of the kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that the complex natural product homoharringtonine (HHT) disrupts the PPI between CDK2 and cyclin A to act as an efficacious anticancer agent, although the allosteric binding mode of HHT has not been experimentally confirmed outside of computational models and its selectivity amongst kinases not explored. 36 Additionally, disrupting the CDK2/cyclin interaction may be less toxic than traditional ATP-site inhibitors that sequester cyclin via their positive cooperativity with cyclin binding. 16 Further development of our allosteric inhibitors might confer an advantage in this regard compared to other promising compounds, such as recently developed CDK2/cyclin E1 inhibitor PF-07104091, a selective ATP-site inhibitor targeting the cyclin-bound activated state of the kinase.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that the residual signal is from nonspecific interactions with the Cdk2-loaded sensor, some of which may be protein aggregation. Other cyclin binding competitive compounds have been reported which are not canonical Type II inhibitors in that they do not induce an inactive conformation of the DFG motif. , We tested Merck compound 14 (MC14), which is a quinoline-based compound developed from a screen of CycA binding inhibitors . It was previously reported that MC14 binds Cdk2 with 5 nM affinity, as determined from temperature-dependent circular dichroism, and destabilizes purified Cdk2-CycA complexes as determined by thermostability experiments .…”
Section: Resultsmentioning
confidence: 99%
“…There have also been reports of a Type II inhibitor, AUZ 454 (or K03861), which binds monomer Cdk2 and stabilizes an inactive conformation of the A-loop DFG motif, and of a class of compounds developed specifically to inhibit Cdk2-cyclin association . Another recent study found that the plant alkaloid and approved drug for leukemia known as homoharringtonine (HHT) inhibits Cdk2-CycA association and promotes autophagic degradation of Cdk2 . A deepened understanding of how inhibitor-kinase association impacts cyclin association and vice versa will be critical for assessing the pharmacological relevance of any given agent.…”
Section: Introductionmentioning
confidence: 99%
“…TRIM21 inhibits the activity of PXR by mediating PXR ubiquitination and degradation (125). Similarly, Cyclindependent kinase 2 (CDK2) complex is hyper activated in most cancers (126,127), TRIM21 mediates the autophagic degradation of CDK2 induced by homoharringtonine limiting the progression of leukemia (128).…”
Section: Role Of Trim21 In Cancer Treatmentmentioning
confidence: 99%